Analisis Gaya Bahasa Yang Terdapat Dalam Lirik Lagu Beranjak Dewasa Karya Nadin Amizah - Lestari, Rigina Dwi Indah; Nazurty, Nazurty; Nurfadilah, Nurfadilah (Universitas Batanghari Jambi, 2024)
This writing aims to describe the language style contained in the lyrics of the song Beranjak Adult by Nadin Amizah. Thisresearch is a qualitative descriptive study, taking data from every word, phrase and clause contained in the lyrics of the song grownup Nadin Amizah. Researchers collected data using listening and note-taking techniques, such as listening to the song BeranjakAdult, then noting the lyrics that contain language styles. The results of this research show several language styles used in songlyrics. The data found was 13 data consisting of 2 comparative language styles, namely 1 simile and 1 antithesis. There is 1polysyndeton data in the conflicting language style. There is 1 polysyndeton language style in the linking language style. Therepetition language style contains 9 data, namely 6 assonances, 1 anaphora, and 2 alliteration. The language style that is mostoften used in Beranjak Adult song lyrics is repetition.